PERBAIKAN MANAJEMEN PEMELIHARAAN KERBAU MURRAH SEBAGAI PENGHASIL SUSU DAN DADIH DI KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Elly Roza; Yulia Yellita; Elihasridas Elihasridas; Ade Rakhmadi; Rizqan Rizqan (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
The community service program is conducted at the Kelok Rambai livestock Group, Kapau, Tilatang Kamang District, Agam Regency. the Kelok Rambai livestock Group is a group of livestock that raises Murrah buffalo but has not implemented good maintenance management. Maintenance management that has not been appropriately managed and farmers' lack of knowledge are the main obstacles faced at the service location. The productivity of Murrah buffalo is still very low. This service activity aims to improve maintenance management, improve the income of Murrah buffalo farmers with the application of good management, and the application of science and technology and research results to develop independent businesses. The method of activities carried out in this service is participatory community empowerment, including counseling, training/ pilots, guidance/ guidance, discussion/ consultation, and evaluation/monitoring. It is hoped that from community service activities to Kelok Rambai livestock Group, it can increase income for group members, implement good maintenance management, increase motivation, use appropriate technology and make Kapau one of the central Murrah buffalo farms producing milk and “dadih” in West Sumatra.